Florid Cemento-Osseous Dysplasia at the Site of Previous Teeth Extraction: Report of a Case - Akhlaghi, Fahimeh; Bemanali, Mehdi; Dehghani, Nima (Journal of Dental School, 2019)
Objective: Florid cemento-osseous dysplasia (FCOD) is a rare bone lesion that predominantly involves the women’s jaws in middle age. This condition is usually asymptomatic and has a benign course. Case: This paper presents a rare case of FCOD in a white middle aged woman, which had affected mandible bilaterally and was diagnosed after tooth extraction and treated conservatively. We believed tooth extraction was a contributing factor for outbreak of such a lesion in this susceptible patient. Conclusion: For the asymptomatic patients, the best management consists of regular recall examinations with prophylaxis and reinforcement of oral hygiene to prevent periodontal diseases and tooth loss, but with accession of clinical signs and symptoms, surgical intervention is inevitable.